Requirements engineering (RE) process for the adaptation of hospital information system (HIS) - Abd Malik, Sofianiza; Nordin, Azlin; Al-Ehaidib, Reem Nasser (Insight Society, 2019)
Requirements Engineering (RE) process is an initial stage for any software development process. In this research, we adopted the RE process into a system adaptation software project for a Hospital Information System (HIS). Instead of developing from scratch, the adaptation of an existing system enables a working system to be configured into use in a similar situation in another organization, or use it in a different organization in a different geographical area. Nonetheless. the approach of systems adaptation has its own issues and challenges. This research considers investigating culture-specific behaviour when adapting a system to another environment. The research is motivated by the challenges faced by real-life cases of implementation of a HIS developed in South Korea at one of Saudi Arabian hospital. The outcome of the research is validated through evaluation of academic experts and feedback from a request tracking system. The contribution of the research outcome provides an insight to facilitate the HIS adaptation into Saudi Arabia HIS, and could also be used as a reference for any adaptation process to suit the needs of the stakeholders in similar application domains.